Letting go in Islamic psychology: integrating ikhtiar, tawakkal, and acceptance - Nikmah Rochmawati; Siti Nur Lailatul Qodriyah; Mohammad Dzul Fahmi Al Ghozali; Siti Aisyah Panatik (Universitas Ahmad Dahlan, 2026)
This literature review examines the current state of research on the concept of letting go within the framework of Acceptance and Commitment Therapy (ACT) and Islamic psychology. While previous studies have explored letting go as psychological acceptance and emotional regulation in Western psychotherapy, there remain gaps in understanding its integration with spiritual and transcendental dimensions, particularly within Muslim populations. The review synthesizes empirical and conceptual findings from peer-reviewed studies published between 2016 and 2026, retrieved from DOAJ, Scopus-indexed journals, and other relevant scientific databases. Major themes identified include ikhtiar as purposeful effort, tawakkal as reliance on God, sabr as patience in adversity, and ridha as spiritual acceptance of outcomes. The review highlights that these constructs correspond with psychological flexibility in ACT, while also extending it by incorporating religiosity-based meaning-making processes. Methodological trends indicate a predominance of qualitative and conceptual studies, with limited empirical and longitudinal research. Theoretically, the integration of Islamic psychology and ACT offers a culturally grounded expansion of acceptance-based models. Practically, the findings provide a foundation for developing culturally sensitive psychological interventions for Muslim populations. This review underscores the need for future research employing experimental designs, longitudinal approaches, and psychometric instrument development within the domain of Islamic psychological flexibility.